(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Autism spectrum disorder (ASD) is common in children with blindness. Differentiating between autistic-like features related to blindness and “true” autistic features can be very difficult, and demands clinical experience of children with blindness and their typical development, as well as properly adapted assessment tools. The purpose of this study was to present an overview of the characteristics of blindness and ASD. A literature review was performed according to PRISMA criteria. Publications from ERIC, EBSCO-Host, Science-Direct, PROQUEST, SCOPUS, and Google Scholar have been analysed. Recent research has indicated that the prevalence of ASD may be higher in individuals with visual impairments (48%) than in the general population (1.5%), and the risk of ASD increases with the severity of visual impairment. Also, research has shown that certain aetiologies of blindness seem to have especially high comorbidity with ASD, mainly optic nerve hypoplasia, retinopathy of prematurity, and anophthalmia.